If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + -1 = -6 + x Combine like terms: -9 + -1 = -10 -10 = -6 + x Solving -10 = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + -1x = -6 + x + -1x Combine like terms: x + -1x = 0 -10 + -1x = -6 + 0 -10 + -1x = -6 Add '10' to each side of the equation. -10 + 10 + -1x = -6 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = -6 + 10 -1x = -6 + 10 Combine like terms: -6 + 10 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| n+14+6n-52=32 | | 10-(8-Q)=20-2*Q | | -8x+7+9x=-23+21 | | -3-12=5x+16-4x | | 7x+17-6x=-4-11 | | 4n-20-7n+16-3=35 | | abs(5x-3)-9=0 | | 3x(3x-1)=30 | | -5(2x-2)=2(1-4x) | | 3u+2w=11 | | 7-3a=-2(-7+2a) | | 3n-5+6n-17=167 | | 2(1+7r)+5r=2+7r | | x^2=-24x | | -2-4a=6-a-3a | | -2-4a=6-a | | 6-7x=-7+6 | | (x-y)(x^2-7xy+y^2)=0 | | 30x+2=902 | | 31=-8(3n-2)-3(4+n) | | (3v^4+6v)-5v^4-4v+8= | | -6=-4x+7x | | (6x+11)*log(4)=(x-1)*log(16) | | 103=8(7-m)+7 | | 4n+42+n-100=2942 | | 103=8(3n-2)-3(4+n) | | 4z=1.7+4.3 | | x^2-3*x=22 | | x^2-3*tan(4*3x)=12 | | 5+3a+3=23 | | 0.8p=-112 | | x+9-2sqrtx+24=0 |